Changes in Techno-Functional Characteristics of Cow Colostrum Powder Prepared by Freeze Drying - Anamika Das; Raman Seth; Ayon Tarafdar; Swarnima Dey; Yogesh Kumar; Ranjna Sirohi (Journal of Food Quality)
The present study investigates the characteristics of freeze-dried bovine colostrum powder prepared from the first three milkings of Karan fries cattle at different intervals. Bioactive components of bovine colostrum are heat sensitive, and therefore, in order to retain the biological activity of different components, it should be subjected to minimal nonthermal treatment. In this study, the optimum temperature/time combination of 60°C/45 min was used for the processing of cow colostrum. At this temperature, the microbial count significantly decreased as compared to raw colostrum. In freeze-dried bovine skimmed colostrum powder (BSCP) and bovine colostrum whey powder (BCWP), IgG emerged as the highest fraction among immune factors, whereas in growth factors, insulin-like growth factor 1(IGF1) and transforming growth factor β2 (TGFβ2) were found in large proportion as compared to insulin-like growth factor 2 (IGF2) and transforming growth factor β1 (TGFβ1). The IgG content (per 100 g) of BSCP prepared from 1st, 2nd, and 3rd milking was found to be 36.62, 27.87, and 20.51 g, respectively, whereas IgG content (per 100 g) of BCWP prepared from 1st, 2nd, and 3rd milking was found to be 33.32, 24.53, and 16.81 g, respectively. The IGF1 content (per 100 g) of BSCP prepared from 1st, 2nd, and 3rd milking was found to be 921.6, 741.2, and 617.2 μg, respectively, whereas IGF1 content (per 100 g) of BCWP prepared from 1st, 2nd, and 3rd milking was found to be 869.8, 688, and 454.4 μg, respectively. The TGFβ2 content (per 100 g) of BSCP prepared from 1st, 2nd, and 3rd milking was found to be 1278, 1076, and 856.8 μg, respectively, whereas TGFβ2 content (per 100 g) of BCWP prepared from 1st, 2nd, and 3rd milking was found to be 1167, 950.2, and 769.2 μg, respectively. The microstructure of freeze-dried cow colostrum whey powder revealed that its pore size was more than that of skimmed colostrum powder. BCWP exhibited lower phagocytic activity as well as lymphocyte proliferation index as compared to BSCP which was carried out in vitro. The observations of the study provide an insight about the components present in BCWP and BSCP apart from the physical characteristics of the products which might pave the way for its utilization in various food formats.